MYC Overexpression at the Protein and mRNA Level and Cancer Outcomes among Men Treated with Radical Prostatectomy for Prostate Cancer - Pettersson, Andreas; Gerke, Travis; Penney, Kathryn L.; Lis, Rosina T.; Stack, Edward C.; Pértega-Gomes, Nelma; Zadra, Giorgia; Tyekucheva, Svitlana; Giovannucci, Edward L.; Mucci, Lorelei A.; Loda, Massimo (Cancer epidemiology, biomarkers & prevention, 2018)
Background: The proto-oncogene MYC is implicated in prostate cancer progression. Whether MYC tumor expression at the protein or mRNA level is associated with poorer prognosis has not been well studied. Methods: We conducted a cohort study including 634 men from the Physicians' Health Study and Health Professionals Follow-up Study treated with radical prostatectomy for prostate cancer in 1983–2004 and followed up for a median of 13.7 years. MYC protein expression was evaluated using IHC, and we used Cox regression to calculate HRs and 95% confidence intervals (CIs) of its association with lethal prostate cancer (distant metastases/prostate cancer–related death). We assessed the association between MYC mRNA expression and lethal prostate cancer in a case–control study, including 113 lethal cases and 291 indolent controls. Results: MYC nuclear protein expression was present in 97% of tumors. MYC protein expression was positively correlated with tumor proliferation rate (r = 0.37; P < 0.001) and negatively correlated with apoptotic count (r = −0.17; P < 0.001). There were no significant associations between MYC protein expression and stage, grade, or PSA level at diagnosis. The multivariable HR for lethal prostate cancer among men in the top versus bottom quartile of MYC protein expression was 1.09 (95% CI, 0.50–2.35). There was no significant association between MYC mRNA expression and lethal prostate cancer. Conclusions: Neither MYC protein overexpression nor MYC mRNA overexpression are strong prognostic markers in men treated with radical prostatectomy for prostate cancer. Impact: This is the largest study to examine the prognostic role of MYC protein and mRNA expression in prostate cancer. Cancer Epidemiol Biomarkers Prev; 27(2); 201–7. ©2017 AACR.